2011
DOI: 10.1002/pola.25857
|View full text |Cite
|
Sign up to set email alerts
|

Deprotection‐free preparation of propargyl ether‐containing phosphinated benzoxazine and the structure–property relationship of the resulting thermosets

Abstract: Generally, protection and deprotection procedures of amino groups are required in preparing propargyl ether-containing benzoxazines. In this study, we report a facile, deprotection-free preparation of a propargyl ether-containing phosphinated benzoxazine (2) from the nucleophilic substitution of a phenolic OH-containing phosphinated benzoxazine (1) and propargyl bromide in the catalysis of potassium carbonate. The structure of (2) was characterized and confirmed by a high-resolution mass spectrum, 1H, 13C, 1H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Figure (A) shows the chemical structure changes in RT‐FTIR spectrogram at different temperature in KBr disk. When the temperature raised to 250°C, the appearance of band at 3600 cm −1 was attributed to phenolic hydroxyl groups and the stretching vibration of ether at 1250 cm −1 disappeared, which was caused by the exothermic Claisen rearrangement of allyl ether groups . Additionally, thermograms were obtained by scanning the sample twice from 30°C to 280°C with a heating rate of 10°C min −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure (A) shows the chemical structure changes in RT‐FTIR spectrogram at different temperature in KBr disk. When the temperature raised to 250°C, the appearance of band at 3600 cm −1 was attributed to phenolic hydroxyl groups and the stretching vibration of ether at 1250 cm −1 disappeared, which was caused by the exothermic Claisen rearrangement of allyl ether groups . Additionally, thermograms were obtained by scanning the sample twice from 30°C to 280°C with a heating rate of 10°C min −1 .…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Incorporation of another polymerizable group to benzoxazine compounds could increase the crosslinking densities and the glass transition temperatures (T g ) of the corresponding polybenzoxazines. [13][14][15][16] Phosphorylation of benzoxazines improves the ame retardancy of the corresponding polymers. [16][17][18][19] The benzoxazines possessing hydroxyl 20,21 and carboxylic acid 22,23 groups exhibit relatively low polymerization temperatures and good processing properties.…”
Section: Introductionmentioning
confidence: 99%
“…The methylphosphine oxide‐containing PBZ exhibited a LOI value of 38 . The cyclic organic phosphorus 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO)‐containing PBZs also achieved UL‐94 V‐0 grade . Interestingly, it was found that the incorporation of halogens and P elements did not appear to fulfill environmentally friendly flame retardation due to abovementioned problems.…”
Section: Introductionmentioning
confidence: 99%